An unusual cause of dementia. Issue 838 (August 1995) - Vassallo, M.; Allen, S.
Abstract : Gliomatosis cerebri is a rare cerebral tumour that presents with personality and mental state changes. Diagnosis can be very difficult and many times is made at post mortem. We describe a 63-year-old man who presented initially with depression that merged into a schizophrenia-like illness, and who developed progressive dementia prior to his death. Two computed tomography (CT) scans of the brain were normal and the diagnosis of gliomatosis cerebri was made at post mortem. The progressively changing mental state was suggestive of an organic cause of his illness. Since this tumour may not be detected by a CT scan, a magnetic resonance imaging scan with T2-weighted images with spin echo sequences of the brain should be performed. Prognosis is very poor but diagnosis is important to plan terminal care. The patient described was unusual because he was older than most people with this tumour, and he presented with psychiatric symptoms which were thought to be non-organic for almost two years.